Integrasi Model Plan-Do-Check-Act dan Supervisi Akademik dalam Penguatan Kapasitas Guru Sekolah Dasar - Kusmiati, Iis; Hidayat, Hidayat (Cetta: Jurnal Ilmu Pendidikan, 2025)
Improving the quality of primary education in Indonesia requires strengthening teacher capacity as a key element in classroom learning. Within the context of the Merdeka Curriculum, school principals play an increasingly strategic role in supporting teachers through the PDCA (Plan-Do-Check-Act) quality management approach. This study aims to analyse the contribution of school principals in enhancing teacher competence through PDCA-based mentoring. A qualitative approach with a case study design was employed in two public primary schools: SDN Pondoksirap, Bandung Regency, and SDN 045 Pasirkaliki, Bandung City. Data were collected through in-depth interviews, participatory observation, and documentation, and were analysed thematically based on the PDCA stages. The findings indicate that mentoring plans were designed based on actual teacher needs; academic supervision and training were conducted in a participatory and contextual manner; and evaluation and follow-up were implemented reflectively. Teachers reported increased motivation, confidence, and active engagement in the learning process. The PDCA approach proved effective in fostering a collaborative and adaptive learning ecosystem. Despite challenges such as limited time and resources, school principals employed adaptive strategies to overcome these barriers. The study concludes that PDCA-based mentoring by school principals contributes significantly to the sustainable improvement of teacher professionalism and offers important implications for teacher development policies and school leadership that are responsive to curriculum dynamics and local needs.